Fraud - Jizi, Mohammad (2017)
Because of the recent collapse of several major companies, investors' confidence in audited financial statements has decreased significantly. Fraud has been a major topic among many scholars and stakeholders due to its importance and impact on financial statements and economies at large. This study examines auditors' responsibility in fraud detection. The results of such an examination highlight the differences between the perception of fraud by audit trainees and by experienced auditors. Gender differences are also highlighted in relation to fraud procedures and perception of fraud. External auditors in the Middle East are aware, to a certain extent, of their responsibilities regarding fraud detection and prevention. Audit work is conducted in relative compliance with established auditing standards. Additional testing that is over and above their responsibilities is being done in some cases due to auditors' concerns for their reputation. This paper fulfils a resource need for academics and practitioners. It indicates that the existence of fraud in the Middle East is not linked to auditors' misunderstanding of their responsibilities, but might be attributed to the corporate culture and environment.